2013
DOI: 10.1186/1471-2393-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fetal nasal bone length measurement at 11–14 weeks of gestation

Abstract: BackgroundNasal bone assessment has been incorporated into Down syndrome screening in first trimester. Several studies have established the normal reference values for fetal nasal bone length in the first trimester, which were found to be varied by population. However, the study on reliability of nasal bone length measurement was limited with contradictory results. This study aimed to investigate the reliability of fetal nasal bone length measurement at 11–14 weeks of gestation in the Thai population.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
20
1
Order By: Relevance
“…CSS is often used in myometrial culture media [3739]. Having observed a culture-induced increase in PR-A expression (and thus PR-T expression ), we examined whether supplementing media with 5% CSS affected culture-induced changes in PR expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSS is often used in myometrial culture media [3739]. Having observed a culture-induced increase in PR-A expression (and thus PR-T expression ), we examined whether supplementing media with 5% CSS affected culture-induced changes in PR expression.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies utilizing myometrial culture (explants) often included CSS in their media [3739]. Therefore, we examined whether supplementing culture media with 5% CSS affected culture-induced changes in PR isoform expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the variability of diagnostic results of gynecological and obstetric sonography in various fields. The knowledge of interobserver variability is of importance for every operator‐dependent diagnostic test, as the widespread use of the diagnostic method depends on the concordance of the examiners' results.…”
Section: Discussionmentioning
confidence: 99%
“…NB has been measured mostly by 2D ultrasound at the 11 to 14 weeks scan, but the results on the reproducibility of these measurements are conflicting. Although some Authors have reported good interobserver agreement, others demonstrated that the reproducibility of NB length assessed by 2D ultrasound at 11 to 14 weeks is inadequate . On the other hand, a reliable reference chart for fetal NB length at 11 to 14 weeks scan is mandatory to assess if the sonographic demonstration of a small NB in the first trimester would increase the risk of trisomy 21.…”
Section: Discussionmentioning
confidence: 99%